2021
DOI: 10.1038/s41535-021-00365-y
|View full text |Cite|
|
Sign up to set email alerts
|

Vital role of magnetocrystalline anisotropy in cubic chiral skyrmion hosts

Abstract: Magnetic anisotropy is anticipated to govern the formation of exotic spin textures reported recently in cubic chiral magnets, like low-temperature tilted conical and skyrmion lattice (SkL) states and metastable SkLs with various lattice geometry. Motivated by these findings, we quantified the cubic anisotropy in a series of CoZnMn-type cubic chiral magnets. We found that the strength of anisotropy is highly enhanced towards low temperatures. Moreover, not only the magnitude but also the character of cubic anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…The drift velocity of a skyrmion is given by where is the velocity of the conduction electrons. The parameters are given as follows 6 , 30 : dissipative force 5.577 , damping factor 0.05, nonadiabatic coefficient 0.03, pinning term with the pinning velocity = 3.2, lattice constant a = 6.32 , local magnetic moment M = 1, and spin polarization p = 0.1 which was estimated from the ratio of magnetizations in the skyrmion phase to the saturated magnetization at 2 K 24 , 30 .…”
Section: Methodsmentioning
confidence: 99%
“…The drift velocity of a skyrmion is given by where is the velocity of the conduction electrons. The parameters are given as follows 6 , 30 : dissipative force 5.577 , damping factor 0.05, nonadiabatic coefficient 0.03, pinning term with the pinning velocity = 3.2, lattice constant a = 6.32 , local magnetic moment M = 1, and spin polarization p = 0.1 which was estimated from the ratio of magnetizations in the skyrmion phase to the saturated magnetization at 2 K 24 , 30 .…”
Section: Methodsmentioning
confidence: 99%
“…2022, 34, 2108770 The angle θ is measured from the [001] axis as indicated in the inset, which depicts the single crystal under investigation prepared as a thin cylindrical disk. The solid black line shows a fit by uniaxial magnetocrystalline anisotropy, [37][38][39] as described in the text.…”
Section: Stability Of Antiskyrmions Governed By Demagnetization Energ...mentioning
confidence: 99%
“…It is well known that the skyrmion structure usually arises as a result of energy competition among the exchange energy, Dzyaloshinskii-Moriya interaction (DMI), demagnetization energy, magnetic anisotropy and Zeeman energy [8]. Previous studies demonstrated that various types of anisotropy terms (e.g., perpendicular magnetic anisotropy (PMA), easy-plane magnetocrystalline anisotropy and cubic anisotropy) may play a prominent role in modulating the skyrmion structures and enhancing their stability [17][18][19][20][21][22][23][24][25]. For instance, PMA can help create and stabilize skyrmions, regulate their structures [13,17,18,26,27], and even enables the stabilization of skyrmion at zero magnetic field in confined nanostructures [8].…”
Section: Of 14mentioning
confidence: 99%